Revaluation of the Local Product, a Good Opportunity for the Rural Development in Albania - Llazo, Edlira (European Journal of Multidisciplinary Studies, 2016)
Even though agriculture is one of the most important sectors in the Albanian economy, which has employed 40 percent of the labor force, after the fall of communism has been faced with the phenomenon of abandonment, with a poor development and is nowadays in search of developing alternatives. New developing alternatives that use the competing advantages of the sector of agriculture in Albania can be discovered by analysing the characteristics of this sector and confronting them with new developments of the sector in Europe. For this purpose within this study is made a questionnaire with the farmers to notice their key concerns in their work and to understand their readiness to be part of innovative schemes that will revalue the local product and will approach them to the consumer.